Incorporação migrante e a reprodução social: um estudo a partir de mapas sociais de mulheres migrantes no interior de São Paulo - Augusti, Ana Maria Gomes (Universidade Federal de São Carlos, 2025)
This research, result of my Undergraduate Research Project funded by CNPq, investigated the impact of the care workload borne by migrant mothers on their ability to obtain employment in Brazil. Based on the concept of social capital, we started from the hypothesis that caring for young children hinders the development of the social ties necessary for migrant women to access the labor market. The empirical study focused on Latin American migrant women in Araraquara, in the countryside of São Paulo. This qualitative research employed semi- structured interviews and sociograms (visual representations of participants' social networks). The data confirm that migrant mothers have fewer social ties than other groups, deepening the debate on the “motherhood penalty” in migratory contexts. The reproductive burden not only hampers professional growth but also limits the development of social ties that could be converted into paid employment. Only 5% of ties helped mothers find jobs, compared to 26.6% for non-mothers. The study reinforces the importance of public policies aimed at the labor integration of women.
Migrant incorporation and social reproduction: a study of sociograms of migrant women in the state of São Paulo
Keywords: Migração; Gênero; Incorporação; Reprodução social; Capital social; CIENCIAS HUMANAS